Beneficial effects of diclofenac therapy on serum lipids, oxidized low-density lipoprotein and antioxidant defenses in rats - Curcelli, Emilio Carlos [UNESP]; Müller, Sérgio Swain [UNESP]; Novelli Filho, Jose Luiz V. B. [UNESP] (Pergamon-Elsevier B.V. Ltd, 2008)
To study the effects of diclofenac, a nonselective nonsteroidal anti-inflammatory drug (NSAID), on lipid profile, oxidized low-density-lipoprotein (Ox-LDL), serum antioxidant defenses and markers of oxidative stress, male Wistar rats were divided into two groups (n = 10): (C) receiving intramuscularly a single daily dose of saline (NaCl 0.9%), and (AI) receiving intramuscularly a single daily dose of 10 mg/kg diclofenac sodium (C14H10C12NNaO2). After 28 days diclofenac-treated rats had lower Ox-LDL, apoprotein B (apo-B), apo-B/LDL-cholesterol and lipid hydroperoxide than C. Total antioxidant substances and superoxide dismutase were increased in diclofenac-treated rats, while no significant changes were observed in catalase, glutathione peroxidase and nitric oxide. A perincubation test done to examine the possibility of mechanism-based activation showed that diclofenac had no effect on maximal superoxide dismutase velocity, but significantly reduced the Michaelis-Menten (K-M) constant, indicating that diclofenac induced SOD activation increasing substrate linkage affinity to the enzyme-catalytic site. In conclusion, diclofenac had beneficial effects decreasing Ox-LDL and improving antioxidant defense. It appears that the application of this agent may be feasible and beneficial for serum antioxidant protection, which certainly would bring new insights on dyslipidemia control. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: diclofenac; NSAID; Ox-LDL; oxidative stress; superoxide dismutase